Planeamiento estratégico de sistemas de información para mejorar la gestión administrativa del Restaurant Palermo’s - Davila Zuñinga, Jorge Alfredo (2019)
"Strategic planning of information systems to improve the administrative management of Restaurant Palermo's" By: DAVILA ZUÑIGA JORGE ALFREDO Restaurant Palermo's is an institution dedicated to the gastronomic sector in the city of Trujillo. Sector that is increasingly competitive. In the development of the present research project, the current situation of the institution was addressed by proposing a strategic plan that fits the business vision, and improves the management of administrative processes; and in general the improvement of the management and planning of the organization. In the elaboration of the Strategic Planning of Information Systems, the methodology of the National Institute of Statistics and Informatics (INEI) was used. It consists of six chapters; In the first chapter, initial aspects were described for the development of the research such as the problematic reality of the organization, statement of the problem, hypothesis, justification of the study and objectives of the research project; in the second chapter, the background was reviewed, the theoretical - conceptual framework was elaborated and the methodology to be applied was determined; in the third chapter, the materials and methods to be used for the development of the research were described; in the fourth chapter, the results of the application of the methodology were determined; in the fifth chapter, the results found were discussed; and in the sixth chapter, conclusions and recommendations were determined.